Presentation, care and outcomes of patients with NSTEMI according to World Bank country income classification: the ACVC-EAPCI EORP NSTEMI Registry of the European Society of Cardiology - Nadarajah, Ramesh; Ludman, Peter; Laroche, Cécile; Appelman, Yolande; Brugaletta, Salvatore; Budaj, Andrzej; Bueno, Hector; Huber, Kurt; Kunadian, Vijay; Leonardi, Sergio; Lettino, Maddalena; Milasinovic, Dejan; et al. (Oxford Academic, 2023)
Background: The majority of NSTEMI burden resides outside high-income countries (HICs). We describe presentation, care and outcomes of NSTEMI by country income classification. Methods: Prospective cohort study including 2947 patients with NSTEMI from 287 centres in 59 countries, stratified by World Bank country income classification. Quality of care was evaluated based on 12 guideline-recommended care interventions. The all-or-none scoring composite performance measure was used to define receipt of optimal care. Outcomes included in-hospital acute heart failure, stroke/transient ischaemic attack and death, and 30-day mortality. Results: Patients admitted with NSTEMI in low to lower-middle-income countries (LLMICs), compared to patients in HICs, were younger, more commonly diabetic and current smokers, but with a lower burden of other comorbidities, and 76.7% met very high risk criteria for an immediate invasive strategy. Invasive coronary angiography use increased with ascending income classification (LLMICs, 79.2%; upper middle income countries [UMICs], 83.7%; HICs, 91.0%), but overall care quality did not (≥80% of eligible interventions achieved: LLMICS, 64.8%; UMICs 69.6%; HICs 55.1%). Rates of acute heart failure (LLMICS, 21.3%; UMICs, 12.1%; HICs, 6.8%; p < 0.001), stroke/transient ischaemic attack (LLMICS: 2.5%; UMICs: 1.5%; HICs: 0.9%; p = 0.04), in-hospital mortality (LLMICS, 3.6%; UMICs: 2.8%; HICs: 1.0%; p < 0.001) and 30-day mortality (LLMICs, 4.9%; UMICs, 3.9%; HICs, 1.5%; p < 0.001) exhibited an inverse economic gradient. Conclusions: Patients with NSTEMI in LLMICs present with fewer comorbidities but a more advanced stage of acute disease, and have worse outcomes compared with HICs. A cardiovascular health narrative is needed to address this inequity across economic boundaries.
Keywords: Country income; Mortality; NSTEMI; Quality indicators; Registry